Industri Kreatif dan E-Commerce - Javier Syarif Ananta Syahbana; Yuyun Setyawati; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The creative industry has become an important pillar in the modern economy, especially with the emergence of e-commerce as the main platform for distribution and marketing of creative products. This research examines the relationship between creative industries and e-commerce, as well as the impact of their integration on economic growth, job creation and innovation. Through analysis of various case studies and statistical data, it was found that e-commerce not only expands the market reach for creative products but also encourages industry players to improve the quality and diversification of their products. Additionally, the digital technology that supports e-commerce provides tools for creators to interact directly with consumers, collect feedback, and adjust product offerings according to market needs. These findings show that the synergy between the creative industry and e-commerce has great potential to increase overall economic competitiveness.